SPECIFICS OF LEGAL REGULATION DAMAGES CAUSED THE STATE EMERGENCY SERVICE OF UKRAINE FOR FIRE EXTINGUISHING - Khryapinskiy A.P.; Khmyrov I.M. (Pressing Problems of Public Administration, 2016)
The article deals with the features addressed in national legislation the question of compensationthe damage caused by the State Emergency Service for situations in extinguishing  res. It isconcluded that the damage caused by State Emergency Service of Ukraine in extinguishing  res isnot reimbursed in case of following the rules for entering into an individual’s dwelling.